Association between the triglyceride–glucose index and diabetic nephropathy in patients with type 2 diabetes: A cross‐sectional study. Issue 4 (7th September 2020) - Liu, Li; Xia, Rui; Song, Xiaoqing; Zhang, Benping; He, Wentao; Zhou, Xinrong; Li, Shengzhong; Yuan, Gang
Abstract: Aims/Introduction: The triglyceride–glucose (TyG) index has been proposed as a reliable and simple marker of insulin resistance. We investigated the association between TyG index and diabetic nephropathy (DN) in patients with type 2 diabetes. Materials and Methods: A consecutive case series of 682 adult patients with type 2 diabetes hospitalized in the Department of Endocrinology at the Tongji Hospital (Wuhan, Hubei, China) from January 2007 to December 2009 was included in this cross‐sectional analysis. Receiver operating characteristics curve analysis, correlation analysis and multiple logistic regression analysis were carried out. Results: A total of 232 (34.0%) participants were identified with DN. Compared with the non‐DN group, the DN group had longer disease duration, and higher bodyweight, systolic blood pressure, diastolic blood pressure, glycated hemoglobin, triglycerides, total cholesterol, serum uric acid, 24 h‐urinary albumin, TyG index and homeostasis model assessment 2 estimates for insulin resistance (HOMA2‐IR; P  < 0.05 for each). The TyG index with an optimal cut‐off point >9.66 showed a higher area under the receiver operating characteristic curve of 0.67 ( P  = 0.002) than HOMA2‐IR (area under the curve 0.61, P  = 0.029) on receiver operating characteristic curve analysis for DN identification. Additionally, the TyG index positively correlated with the levels of metabolic indicators (bodyweight, glycated hemoglobin, triglycerides, total cholesterol, serum uric acid, fasting glucose and HOMA2‐IR) and natural logarithmic 24 h‐urinary albumin ( P  < 0.05 for each), but not natural logarithm of estimated glomerular filtration rate. On multiple regression analysis, an increased TyG index was shown to be an independent risk factor (odds ratio 1.91, P  = 0.001) for DN. Conclusions: The TyG index was independently associated with DN in patients with type 2 diabetes, and was a better marker than HOMA2‐IR for identification of DN in type 2 diabetes patients. Abstract : The triglyceride–glucose index provides an affordable and easily interpreted biomarker for monitoring the degree of insulin resistance, and was independently associated with diabetic nephropathy in patients with type 2 diabetes. It was a better marker than homeostasis model assessment for insulin resistance for identification of diabetic nephropathy in type 2 diabetes patients.